Low density lipoprotein (LDL) in type 2 diabetes mellitus - Andyanita Hanif Hermawati; Eka Puspitasari; Cholila Lailatul Nurmala (Department of D3 Medical Technology Laboratory STIKes Hutama Abdi Husada Tulungagung, 2019)
Hyperglycemia due to abnormal insulin secretion, insulin work or both. Type 2 Diabetes Mellitus is the most among other types of diabetes mellitus. Diabetes mellitus is usually accompanied by dyslipidemia. Dyslipidemia is a disorder of lipid metabolism or cholesterol characterized by an increase or decrease in lipid fraction in the plasma. Diabetes mellitus and elevated Low-Density Lipoprotein (LDL) cholesterol levels are often found to be interrelated. The purpose of this study was to describe Low-Density Lipoprotein (LDL) levels in patients with type 2 diabetes mellitus. The research design used was descriptive non-analytic. The population in this study were all patients with type 2 diabetes mellitus using a purposive sampling technique of 30 samples. Data collection was carried out by observing the medical record data of type 2 diabetes mellitus patients with Low-Density Lipoprotein (LDL) profile data for 2017. The results showed that patients with type 2 Diabetes Mellitus suffered the most by male sex with a percentage of 57%, aged over 45 years with a percentage of 97%, and having high LDL levels as much as 40%.